Effect of pycnogenol supplementation on blood pressure: A systematic review and meta‐analysis of clinical trials. (21st October 2019) - Pourmasoumi, Makan; Hadi, Amir; Mohammadi, Hamed; Rouhani, Mohammad Hossein
Abstract : Several studies investigated the impact of pycnogenol on blood pressure. Nevertheless, the results are inconclusive. The aim of the present systematic review and meta‐analysis was to clarify the effect of pycnogenol supplementation on blood pressure. PubMed, Scopus, Web of Science, and Google Scholar were systematically searched until March 2018 to find clinical trials, which examined the effect of pycnogenol supplementation on systolic and diastolic blood pressure in adults. A subgroup analysis was applied to find out potential sources of interstudy heterogeneity. A total of 12 clinical trials (922 participants) were included in the meta‐analysis. Pooled analysis suggested that pycnogenol supplementation can reduced systolic blood pressure (SBP) of (‐3.22 mmHg; 95% CI [‐5.52, ‐0.92]) and diastolic blood pressure (DBP; ‐1.91 mmHg; 95% CI [‐3.64, ‐0.18]). Effect of pycnogenol on SBP was more pronounce in subgroup in which pycnogenol was administered along with other treatments. A significant effect of pycnogenol on DBP in studies with >12‐week duration, whereas this favorable effect was not observed in subgroup with ≤12‐week supplementation. The present systematic review and meta‐analysis suggest that pycnogenol had a favorable effect on SBP and DBP. Further, high quality randomized clinical trials are needed to confirm this result.